2014
DOI: 10.1177/0305829814543731
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Principle of (Sovereign) Equality as a Standard of Civilisation

Abstract: The standard of civilisation is most often identified as the infamous legal doctrine that legitimised imperialist rule and the exclusion of non-European non-Christian states from the international society. In disciplinary narratives of both International Relations and International Law this colonial project is usually presented as a mere interlude on the way to a mature and inclusive international society based sovereign equality as its organising principle. In line with more critical historiography, which sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Aalberts has continued the School’s exploration of the interplay between the standards of civilization and international law. However, she treats international law as not only as an institution but an ordering principle, a governmental technology and a form of productive power through which shifting conceptions of legitimate authority are articulated and regulated (Aalberts, 2014: 779).…”
Section: Culture Civilization and The English Schoolmentioning
confidence: 99%
See 2 more Smart Citations
“…Aalberts has continued the School’s exploration of the interplay between the standards of civilization and international law. However, she treats international law as not only as an institution but an ordering principle, a governmental technology and a form of productive power through which shifting conceptions of legitimate authority are articulated and regulated (Aalberts, 2014: 779).…”
Section: Culture Civilization and The English Schoolmentioning
confidence: 99%
“…But here the standards of civilization have become again a site of contestation. As noted above, the promotion of self-determination as a right was fundamental to decolonization and delegitimating the ‘standards of civilization’ as a regulatory framework of sovereignty (Aalberts, 2014). The commensurate reconceptualization of sovereignty fundamentally altered the boundaries and politics of recognition in international society.…”
Section: Culture Civilization and The English Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is a process that is deeply interconnected with empire (Anghie, 2009; Keene, 2002; Reus-Smit, 2013) and, in the more recent past, with other, more or less violent, forms of control and domination. Critical, post-colonial and feminist scholars have shown that these include economic and financial standards (Chimni, 2006; Mozaffari, 2002), hierarchies generated by international law (Aalberts, 2014, Anghie, 2009; Pahuja, 2011), relations of gender dominance (Towns, 2009; Yuval-Davis, 1997), racial hierarchies (Sabaratnam, 2017; Yunis, 2018), stratifications of class (Agathangelou and Ling, 2009; Pal, 2018) and nationality (Chatterjee, 1993, 2010). A number of scholars have further stressed that, historically, resistance has been as central a pattern as domination in the making of the international system (Crawford, 2002; Lake and Reynolds, 2008; Meger, 2017).…”
Section: The Disjuncture Between the Expansion Of International Sociementioning
confidence: 99%
“…Practices such as peacekeeping and peacebuilding, in such a view, have become institutionalized tools in a broader process in which sovereignty has become governmentalized (Aalberts, 2014; Andersen and Sending, 2010; Bartelson, 2014; Zanotti, 2011), itself a tool for restoring order in areas where ‘forms of political authority still refuse to be squeezed into the symbolic form of sovereignty’ (Bartelson, 2014: 89). No longer absolute, but contingent upon ‘proper’ state behaviour, sovereignty today becomes the prize of good behaviour, but also the blueprint or prescription for how to craft polities coming out of longer periods of protracted conflict (Andersen and Sending, 2010).…”
Section: Introductionmentioning
confidence: 99%